Cobalt ions loaded polydopamine nanospheres to construct ammonium polyphosphate for the improvement of flame retardancy of thermoplastic polyurethane elastomer. (August 2022) - Li, Yi-Ran; Li, Ying-Ming; Hu, Wen-Juan; Wang, De-Yi
Highlights: A highly efficient and halogen-free flame retardant Co-PDA-APP was prepared by modifying the surface of ammonium polyphosphate (APP) with dopamine (DA) and cobalt ions (Co). Co-PDA-APP can significantly improve the flame retardancy of TPU by working in the condensed and gas phases. The tensile strength of flame-retarding composites was 24.4 MPa, which was preserved at a high level comparing to that of TPU/APP3 composites. Abstract: Fire safety and environmental friendliness are the two key factors for the industrial application of polymer-based composites; hence, highly efficient and halogen-free flame-retarding polymer composites have been developed to achieve the above attributes. In the present work, halogen-free flame retardant Co-PDA-APP was prepared by modifying the surface of ammonium polyphosphate (APP) with dopamine (DA) and cobalt ions (Co) to enhance the fire safety of thermoplastic polyurethane elastomer (TPU). When only 3 wt% of Co-PDA-APP was added, the limiting oxygen index (LOI) reached to 25% and passed the V-0 rating in UL-94 test. The peak of heat release rate (PHRR) and peak of smoke production rate (PSPR) decreased by 66.0% and 76.4% comparing to the relative values of neat TPU. Moreover, thermogravimetry Fourier-transform infrared and Raman spectroscopy were carried out to investigate the flame-retardant mechanism of Co-PDA-APP in the TPU composite. The intumescent flame-retardant mechanism was found to be dominant, and APP, PDA, and Co promoted the formation of a physical barrier and enhanced the fire safety of the TPU composite. Furthermore, the tensile strength was 24.4 MPa, which was preserved at a high level comparing to that of TPU/APP3 composites.